Integration of human adipocyte chromosomal interactions with adipose gene expression prioritizes obesity-related genes from GWAS - David Z. Pan (Nature Portfolio, 2018)
GWAS have identified numerous genetic loci for BMI and related traits. Here, Pan et al. generate Promoter Capture Hi-C data for human white adipocytes and integrate these with data of transcription factor motifs, RNA-seq and GWAS to identify eQTL-eGene relationships mediated by chromosomal interactions.